Detection of CNX cyanogen halides (X = F, Cl) on metal-free defective phosphorene sensor: periodic DFT calculations. (16th February 2021) - Ghadiri, Mahdi; Ghambarian, Mehdi; Ghashghaee, Mohammad
ABSTRACT: Great research interest in the novel P-based nanosensors has been spurred by the arrival of black phosphorus monolayer devices in recent years. The paper investigates the detection capabilities of defective phosphorene (DP) toward the sensing of cyanogen fluoride and chloride molecules using periodic density functional theory. As found from the optimizations, the analyte stabilisation in the lowest-energy configuration is non-linear with the molecule interacting through the nitrogen head. The fluoride molecule released 2.5 times higher energy (–15.63 kcal/mol at HSE06/TZVP) than the chloride counterpart upon the adsorption on the surface. Significant changes were seen in both spin gaps of DP with sensing, particularly in the case of CNCl. The sensitivity and air selectivity for the system under consideration amounted to 9.9 and 50.4, respectively. Overall, the findings reported herein confirmed that the defective phosphorene (DP) sensor can be used for cyanogen halides detection, with the recovery time of up to 290.0 ms at 298 K. GRAPHICAL ABSTRACT: